Dose-dependent effects of genistein on bone homeostasis in rats' mandibular subchondral bone - Li Yong-qi; Xing Xiang-hui; Wang Hui; Weng Xi-li; Yu Shi-bin; Dong Guang-ying (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of genistein on bone homeostasis in mandibular subchondral bone of rats. Methods: Female SD rats were administered with genistein (10 and 50 mg/kg) or placebo by oral gavage for 6 weeks. Then the animals were sacrificed, and histomorphology and micro-structure of mandibular condyle were examined using HE staining and micro-CT analysis, respectively. The expression levels of alkaline phosphatase (ALP), osteocalcin (OC), osteoprotegerin (OPG), the receptor activator of nuclear factor κB ligand (RANKL) and estrogen receptors (ERs) in mandibular condyle were detected using real-time PCR. Cultured osteoblasts were prepared from rat mandibular condyle for in in vitro study. The cells were treated with genistein (10−7 or 10−4 mol/L) for 48 h. The expression of the bone homeostasis-associated factors and estrogen receptors (ERs) was detected using real-time PCR, and ER silencing was performed. Results: At both the low- and high-doses, genistein significantly increased the bone mineral density (BMD) and bone volume, and resulted in thicker subchondral trabecular bone in vivo. In both in vivo and in vitro study, the low-dose genistein significantly increased the expression of ALP, OC and OPG, but decreased the expression of RANKL and the RANKL/OPG ratio. The high-dose genistein decreased the expression of all these bone homeostasis-associated factors. Both the low and high doses of genistein significantly increased the expression of ERβ, while ERα expression was increased by the low dose genistein and decreased by the high dose genistein. ERβ silencing abrogated most of the effects of genistein treatment. Conclusion: In rat mandibular condylar subchondral bone, low-dose genistein increases bone formation and inhibit bone resorption, while excess genistein inhibits both bone formation and resorption. The effects of genistein were predominantly mediated through ERβ.